2003
DOI: 10.1614/0043-1745(2003)051[0532:drowst]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of weed species to added nitrogen

Abstract: Information on responses of weeds to various soil fertility levels is required to develop fertilizer management strategies as components of integrated weed management programs. A controlled environment study was conducted to determine shoot and root growth response of 23 agricultural weeds to N fertilizer applied at 0, 40, 80, 120, 180, or 240 mg kg−1 soil. Wheat and canola were included as control species. Shoot and root growth of all weeds increased with added N, but the magnitude of the response varied grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
194
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(218 citation statements)
references
References 24 publications
18
194
2
2
Order By: Relevance
“…In greenhouse studies (Blackshaw et al 2003), kochia shoot and root biomass response was similar to or greater than canola, respectively, to increasing amounts of N; the species was among the most responsive weeds to N (Lugg et al 1983). Kochia root plus shoot N uptake comprised about 90% of soil available N (Blackshaw et al 2003).…”
Section: Response To Other Human Manipulationsmentioning
confidence: 88%
See 1 more Smart Citation
“…In greenhouse studies (Blackshaw et al 2003), kochia shoot and root biomass response was similar to or greater than canola, respectively, to increasing amounts of N; the species was among the most responsive weeds to N (Lugg et al 1983). Kochia root plus shoot N uptake comprised about 90% of soil available N (Blackshaw et al 2003).…”
Section: Response To Other Human Manipulationsmentioning
confidence: 88%
“…In greenhouse studies (Blackshaw et al 2003), kochia shoot and root biomass response was similar to or greater than canola, respectively, to increasing amounts of N; the species was among the most responsive weeds to N (Lugg et al 1983). Kochia root plus shoot N uptake comprised about 90% of soil available N (Blackshaw et al 2003). In similar greenhouse studies investigating response to P fertilizer, kochia shoot and root biomass responded less than wheat or canola to added fertilizer P (5Á60 ppm); however, shoot biomass did increase by two-to threefold in response to fertilization relative to the unfertilized control (Blackshaw et al 2004).…”
Section: Response To Other Human Manipulationsmentioning
confidence: 88%
“…In an interference study between domesticated B. rapa and tartary buckwheat (Fagopyrum tataricum L.) where B. rapa was grown as the crop, O'Donovan (1994) found that B. rapa reproductive output was least affected at high B. rapa densities (200 plants m (2 ) compared with lower densities (50 and 100 plants m (2 ). Blackshaw et al (2003) compared shoot and root growth of 23 agricultural weeds and the crop B. napus to a range of N fertilizer rates from 0 to 240 mg kg (1 soil in a controlled environment study. Shoot biomass production of B. napus and of 10 other species [e.g.…”
Section: Response To Other Human Manipulationsmentioning
confidence: 99%
“…The specific weed is a nitrophilous plant and, therefore, responds to nitrogen fertilization very well (Nelson, 2015). Finally, Nutrisphere 100% treatment resulted in the higher total biomass, a finding rather anticipated, as it is generally known that biomass of all weed species tend to increase under nitrogen fertilization (Blackshaw et al, 2003).…”
Section: Resultsmentioning
confidence: 80%